Microbiological Assay for the Determination of Colistin Sulphate - Calixto, Giovana [UNESP]; Domingos, Luciana Elisete; Fabri, Nathalie Thomazini; Carmo, Thais Adriana do; Moreno, Andreia de Haro [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publ Ltd, 2014)
An innovative microbiological assay was developed for the determination of colistin sulphate at various concentrations (192-469 IU/mL); using Bordetella bronchiseptica ATCC 4617 as microorganism test. This assay revealed subtle changes not demonstrated by chemical methods, such as chemical degradation and low of potency, but by evaluating the potency of colistin, which is very important for the analysis of antibiotics. The method was validated according to ICH guidelines, proving to be linear ( r(2) = 0.9985), precise ( CV = 1.32%) and accurate ( 100.9 +/- 1.33%). It was concluded that the microbiological assay is satisfactory for in vitro quantitation of the antibacterial activity of colistin sulphate.
Keywords: Agar diffusion method; Bordetella bronchiseptica; colistin sulphate; method validation; microbiological assay; in vitro quantification